2013
DOI: 10.1111/jace.12393
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide Whiskers: Preparation and High Dielectric Permittivity

Abstract: Silicon Carbide whiskers have been synthesized using silica sol and activated carbon as reagents via microwave heating without the presence of any of the catalysts, such as Fe, Ni, and Al etc.. The synthesized whiskers were separated and concentrated from the as‐synthesized products using the gravity concentration process. The dielectric properties of the concentrated SiC whiskers were investigated in the frequency range 2–18 GHz. The results indicate that the SiC whiskers exhibit higher dielectric permittivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…The diffraction peaks at 35.60°, 59.98°, 71.78°, and 75.49° are indexed to (1 1 1), (2 2 0), (3 1 1), and (2 2 2) planes of β‐SiC, respectively. There is a low‐density peak (marked with stacking faults (SFs)) at the diffraction angle of 33.7°, which reflects the spontaneously formed SFs during the SiC growth. In fact, it has been reported that SFs, twins, and dislocations are very often observed in CVD‐SiC .…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks at 35.60°, 59.98°, 71.78°, and 75.49° are indexed to (1 1 1), (2 2 0), (3 1 1), and (2 2 2) planes of β‐SiC, respectively. There is a low‐density peak (marked with stacking faults (SFs)) at the diffraction angle of 33.7°, which reflects the spontaneously formed SFs during the SiC growth. In fact, it has been reported that SFs, twins, and dislocations are very often observed in CVD‐SiC .…”
Section: Resultsmentioning
confidence: 99%
“…Then the Al-doped SiCw was synthesized at 1500 C for 30 min by using a 2.45 GHz microwave furnace in a flowing argon atmosphere. After that, whiskers were concentrated through a gravity concentration method that is described in a previous work [19]. The prepared sample were heat treated in air at 700 C for 2 h, and then were acid-washed in HFeHNO 3 mixture (HF/HNO 3 ¼ 1:1 in molar ratio).…”
Section: Preparation Of Al-doped Sic Whiskersmentioning
confidence: 99%
“…Compared with other carbon materials, SiC can be used under high-temperature conditions and its loss factor increases with temperature [8−9]. One-dimensional SiC nanowires have been found to possess substantially higher permittivity than SiC nanoparticles [6]. Furthermore, the criteria of being lightweight, thin and absorbing microwaves over a broad frequency bandwidth can be realized by SiC.…”
Section: Introductionmentioning
confidence: 99%